Oxidation of 1-Amidoalkyl-2-naphthols Using (Diacetoxyiodo)benzene: Unusual Formation of 1-Arylnaphtho[1,2-d]isoxazoles - Shelke, Amol V.; Bhong, Bhagyashree Y.; Karade, Nandkishor N. (Synthesis, 2014)
The reactions of 1-amidoalkyl-2-naphthols with (diacetoxyiodo)benzene results in the unusual formation of 1-arylnaphtho[1,2-d]isoxazoles. This procedure demonstrates a useful application of (diacetoxyiodo)benzene for the oxidative formation of an N–O bond.
Keywords: 1,2-benzisoxazole; hypervalent iodine; 1-amidoalkyl-2-naphthols; 2-hydroxyaryl ketoximes; phenolic oxidation